2009
DOI: 10.1101/gr.086546.108
|View full text |Cite
|
Sign up to set email alerts
|

Breakpoint regions and homologous synteny blocks in chromosomes have different evolutionary histories

Abstract: The persistence of large blocks of homologous synteny and a high frequency of breakpoint reuse are distinctive features of mammalian chromosomes that are not well understood in evolutionary terms. To gain a better understanding of the evolutionary forces that affect genome architecture, synteny relationships among 10 amniotes (human, chimp, macaque, rat, mouse, pig, cattle, dog, opossum, and chicken) were compared at <1 human-Mbp resolution. Homologous synteny blocks (HSBs; N = 2233) and chromosome evolutionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

28
220
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(251 citation statements)
references
References 38 publications
28
220
1
2
Order By: Relevance
“…The incorporation of these complex models of genome evolution in ABC techniques is not straightforward because different genomic regions may have evolved under different evolutionary histories (e.g., Larkin et al 2009) and may present a region-specific best-fit evolutionary model (Arbiza et al 2011). Thus, the first stage of an ABC methodology oriented to analyze genomic data accounting for complex genome evolution may involve the identification of those genomic regions that could have evolved under a specific evolutionary history and evolutionary process (Fig.…”
mentioning
confidence: 99%
“…The incorporation of these complex models of genome evolution in ABC techniques is not straightforward because different genomic regions may have evolved under different evolutionary histories (e.g., Larkin et al 2009) and may present a region-specific best-fit evolutionary model (Arbiza et al 2011). Thus, the first stage of an ABC methodology oriented to analyze genomic data accounting for complex genome evolution may involve the identification of those genomic regions that could have evolved under a specific evolutionary history and evolutionary process (Fig.…”
mentioning
confidence: 99%
“…For example, Everts-van der Wind et al (2004) reported that evolutionary breakpoints between the cattle and human genomes are significantly enriched for genes. Recently, this observation was confirmed by multi-species genome comparisons (Murphy et al, 2005;Larkin et al, 2009). Subsequently, Larkin et al (2009) have shown that the amniote-specific EBRs are enriched for genes that involve an organism's response to external stimuli.…”
Section: Decoding Cattle Genomementioning
confidence: 69%
“…Recently, this observation was confirmed by multi-species genome comparisons (Murphy et al, 2005;Larkin et al, 2009). Subsequently, Larkin et al (2009) have shown that the amniote-specific EBRs are enriched for genes that involve an organism's response to external stimuli. In cattle, a cattle-specific EBR is associated with formation of a new bidirectional promoter that may affect control of expression of the CYB5R4 gene.…”
Section: Decoding Cattle Genomementioning
confidence: 69%
See 2 more Smart Citations